Die gelehrte Korrespondenz der Brüder Pez, Text, Regesten, Kommentare Band 1: 1709-1715 - Wallnig, Thomas (2010)
The submitted manuscript for Vol. I. comprises the learned correspondence of the Benedictine historians Bernhard and Hieronymus Pez of Melk abbey from the years 1709 to 1715. The edition and commentary were prepared between 2004 and 2008 within FWF project P-16940 under the direction of Prof. Winfried Stelzer by Thomas Wallnig and Thomas Stockinger at the Institute for Austrian Historical Research, Vienna. The submission of the work for publication is being filed concurrently with the final report on the project to the FWF. The significance of the Pez letters, of which the submitted volume will make roughly one quarter available to the public for the first time, is twofold. On the one hand, the European scope of the correspondence leads to a re-evaluation of the position of Austria and southern Germany within European intellectual history of the early 18th century and within the erudite practice and culture of communication in the Republic of Letters. On the other hand, the prosopographical orientation of the brothers' project (a collection of bio-bibliographical data on Benedictine authors of the 16th to 18th century) provides the beginnings of an inventory and topography of a nearly undiscovered intellectual landscape. The volume contains: an introduction sketching the various monastic and erudite contexts of the correspondence, presenting learned letters as a literary genre, and setting out the principles of the edition; the edition itself, which gives 261 extant letters in the original Latin with critical notes, German summaries and commentary, and which also registers 211 lost letters; an appendix with biographical information on the 82 correspondents and four tables (letters by correspondents, letters in chronological order, items enclosed with the letters, mentioned letters between third persons); sources and bibliography; finally a cumulative bio-bibliographical index. Publication is envisioned within the series "Quelleneditionen des Instituts für Österreichische Geschichtsforschung" (Böhlau publishing house) as the first of four planned volumes of the correspondence. The publication is primarily aimed at researchers in Austrian history, intellectual history and history of education, and ecclesiastical history, but is also potentially of interest to the disciplines of art history, history of publishing, and also to medievalists in view of the numerous mentions of the location and usage of manuscripts. Volume 2: https://e-book.fwf.ac.at/o:824 and https://e-book.fwf.ac.at/o:825